1995
DOI: 10.1139/o95-107
|View full text |Cite|
|
Sign up to set email alerts
|

Structure and function of ribosomal RNA

Abstract: A refined model has been developed for the folding of 16S rRNA in the 30S subunit, based on additional constraints obtained from new experimental approaches. One set of constraints comes from hydroxyl radical footprinting of each of the individual 30S ribosomal proteins, using free Fe(2+)-EDTA complex. A second approach uses localized hydroxyl radical cleavage from a single Fe2+ tethered to unique positions on the surface of single proteins in the 30S subunit. This has been carried out for one position on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 29 publications
2
52
0
Order By: Relevance
“…14 -17) have provided more insight into the protein-RNA interactions and their functional implications within the prokaryotic ribosome. Additionally, site-directed hydroxyl radical probing of the rRNA neighborhood in reconstituted ribosomal particles has provided information relevant to the three-dimensional orientation of several proteins within the 30 S subunit (18,19).Even though discrete peptide regions of individual ribosomal proteins in close contact to the rRNA have been clearly established (13), the analysis of the corresponding sites on the rRNA has still remained a problem. Detailed modeling of ribosomal structures requires precise knowledge of protein-nucleotide and peptide-RNA contact sites concomitantly at the amino acid and nucleotide level.…”
mentioning
confidence: 99%
“…14 -17) have provided more insight into the protein-RNA interactions and their functional implications within the prokaryotic ribosome. Additionally, site-directed hydroxyl radical probing of the rRNA neighborhood in reconstituted ribosomal particles has provided information relevant to the three-dimensional orientation of several proteins within the 30 S subunit (18,19).Even though discrete peptide regions of individual ribosomal proteins in close contact to the rRNA have been clearly established (13), the analysis of the corresponding sites on the rRNA has still remained a problem. Detailed modeling of ribosomal structures requires precise knowledge of protein-nucleotide and peptide-RNA contact sites concomitantly at the amino acid and nucleotide level.…”
mentioning
confidence: 99%
“…Neighborhood of 16S rRNA nucleotides U788/U789 in the 30S ribosomal subunit determined by site-directed crosslinking INTRODUCTION The first secondary structure for the complete 16S rRNA was proposed in 1979 as a result of comparison of the Escherichia coli and Bacillus brevis sequences (Noller, 1980;Woese et al+, 1980)+ Since that time, the secondary structure has been confirmed and elaborated using the large number of sequences in the rRNA database and presently nearly all of the secondary structure base pairs and some tertiary structure base pairs are supported by sequence covariances (Gutell et al+, 1994)+ However, the 16S rRNA sequence comparison does not indicate many covariances between nucleotides distant in its secondary structure that would indicate its three dimensional structure+ Many different approaches have been used to obtain information pertaining to the rRNA higher order structure+ Biochemical experiments that have been most successful are (1) photoaffinity experiments, cleavage experiments, and footprinting experiments utilizing mRNA and tRNA (see Green & Noller, 1997) and (2) structural experiments involving the ribosomal proteins either to obtain footprints for the proteins (Stern et al+, 1989; or by using the proteins to carry cleavage reagents into the subunit Noller et al+, 1995)+ There would be several advantages to studying the rRNA structure with reagents that are in the rRNA+ The rRNA is a highly compact structure (Serdyuk et al+, 1983;Frank, 1997;Stark et al+, 1997), so there should be a high density of RNA-RNA contacts+ Changes in these may be correlated to changes in the ribosome structure, even if there are no changes in RNAribosomal protein contacts+ In addition, data from reporter reagents in the ribosome rather than in mRNA or tRNA substrates will be inherently simpler to use for molecular modeling, since the location and flexibility of the tRNA or mRNA does not have to be considered as part of the modeled structure+ UV light irradiation produces 15 long-range intramolecular crosslinks in the 16S rRNA (Wilms et al+, 1997)+ These provide some new information about its internal three dimensional arrangement and the crosslinking technique provides an opportunity to monitor conformational changes (Noah & Wollenzien, 1998)+ However, the relatively small number of UV crosslinks puts some limits on that approach+ In the present article we describe the use of site-directed crosslinking using a psoralen derivative as the photoreagent (Teare & Wollenzien, 1989)+ In this method, psoralen first is linked to an oligonucleotide, the psoralenoligonucleotide is annealed to the rRNA and the psoralen moiety is phototransferred to the RNA target site+ 16S rRNA containing the psoralen adduct is then purified and reconstituted into 30S subunits+ The advantages of the method are that all the 30S subunits contain psoralen, so the effects of the psoralen on the structure and function of the subunit can be determined independently of the experiments involving crosslinking...…”
mentioning
confidence: 99%
“…The central part of the 30S ribosomal subunit that faces the 50S subunit in the working 70S ribosome contains the region essential for tRNA binding and movement+ Recent cryoelectron microscopy experiments have clearly shown electron density attributable to the tRNAs in the space between the 30S and 50S subunits (Frank et al+, 1995;Agrawal et al+, 1996;Malhotra et al+, 1998)+ The 30S subunit is responsible for mRNA association and the decoding process, and this requires a placement of the anticodon ends of the tRNAs in close proximity with parts of the 30S subunit (Dahlberg, 1989;Noller, 1991;Frank et al+, 1995)+ In terms of the molecular constituents in the 30S decoding region, ribosomal proteins S4, S5, and S12 have been implicated in influencing the fidelity of decoding (see Karimi & Ehrenberg, 1994)+ However, there are a number of 16S rRNA nucleotides that are footprinted by tRNA or at which mutations affect the decoding and translocation process (Noller, 1991)+ Photoaffinity labeling and site specific cleavage experiments by tRNA, tRNA derivatives, and mRNA analogs (see Green & Noller, 1997) also indicate important nucleotide positions+ Several proposals for the three-dimensional arrangement for the 16S rRNA already place many of these sites in positions in the central part of the subunit where they could participate in the expected interactions Noller et al+, 1995;Fink et al+, 1996;Mueller & Brimacombe, 1997;Wang et al+, 1999)+ However, the arrangements still are inconclusive about the proximity of some of the 16S rRNA sites with respect to the bound tRNA, and models are not available yet to describe the details of the binding pockets for the tRNAs+…”
Section: Introductionmentioning
confidence: 99%